2013
DOI: 10.1584/jpestics.w13-05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two successive annual treatments of two systemic insecticides, imidacloprid and fipronil, on dragonfly nymph communities in experimental paddies

Abstract: The effects of two successive annual treatments of imidacloprid and fipronil on dragonfly nymph communities, which are one of the best-known bioindicators in Japanese agroecosystems, were monitored in experimental paddies.e abundance of dragon y nymphs was lower in both insecticides-treated elds than it was in the controls, particularly following pronil treatments. Residues of both insecticides were found in the soil throughout the two years, and imidacloprid persisted in water up to three months following eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Our findings strongly suggest that fipronil application is a major cause of the sharp decline of dragonfly populations in Japanese paddy fields, in agreement with previous research 11 12 13 14 27 . Our mesocosm experiments showed that fipronil application to nursery boxes resulted in a severe decrease in the number of individuals and exuviae of two dragonfly species ( Figs 4 & 5 ), supporting fipronil’s adverse effects on dragonflies.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings strongly suggest that fipronil application is a major cause of the sharp decline of dragonfly populations in Japanese paddy fields, in agreement with previous research 11 12 13 14 27 . Our mesocosm experiments showed that fipronil application to nursery boxes resulted in a severe decrease in the number of individuals and exuviae of two dragonfly species ( Figs 4 & 5 ), supporting fipronil’s adverse effects on dragonflies.…”
Section: Discussionsupporting
confidence: 93%
“…However, S . frequens abundance has declined by 1% over the past 20 years [ 5 ], and several reports suggest that nursery-box application of fipronil is a major cause of the decline of dragonfly nymph numbers in rice paddy fields [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to standard application methods specified by insecticide manufacturers, these insecticides are applied to nursery-boxes only once before transplantation and continue to control pests for several months via systemic or slow effects. Fipronil and imidacloprid concentrations in paddy water and soil reach a maximum and dissipate to half within 3 d after transplantation [ 33 34 , 40 41 ], but these compounds tend to remain stable in the soil at high concentration [ 6 ]. Meanwhile, the eggs of S .…”
Section: Introductionmentioning
confidence: 99%
“…Several possible explanations may account for these results, either alone or in combination. First, although residues of imidacloprid and fipronil likely remained in the soil of the conventional paddies (Hayasaka et al, 2012b(Hayasaka et al, , 2013, and pesticide applications negatively affect ground-dwelling wolf spiders in summer (Oyama and Kidokoro, 2003), these pesticides may not be absorbed by the ground predators through prey-predator interactions during the dry period. Second, because conventional paddies surrounded the sampled organic and herbicide paddies, these paddies may have been affected by the agrochemicals applied to the conventional paddies via leaching or aerial pesticide application (Reichenberger et al, 2007), preventing differences in agrochemical exposures within the arthropod communities.…”
Section: Conventionalmentioning
confidence: 99%
“…The negative effects of pesticides on nontarget aquatic organisms are known in paddy ecosystems (Relyea, 2005;Hayasaka et al, 2012aHayasaka et al, , 2012b, where pesticide residues can accumulate in soil for more than a year (Hayasaka et al, 2013). Pesticide residues in soil may have delayed effects on ground arthropods utilizing paddy fields during the dry season by direct contacts with residues or through the interactions with soil invertebrates that have absorbed agrochemicals.…”
Section: Introductionmentioning
confidence: 99%